THE DEVELOPMENT OF HARVEST STRATEGIES FOR TROPICAL TUNA IN INDONESIA’S ARCHIPELAGIC WATERS - Fayakun Satria; Lilis Sadiyah (Research Center for Fisheries, 2018)
Significant roles of the fishery in the Indonesia’s archipelagic waters/IAW (FMAs 713, 714 and 715), with proportion of around 60% came from the IAW, and a strong residential behavior for skipjack (SKJ) and yellowfin tuna (YFT) encourage Indonesia to develop harvest strategies for the tropical tuna in the IAW. This is a priority action of the National Tuna Management Plan (NTMP) for tropical and neritic tuna. Fisheries operating in the IAW are mainly small scale commercial vessels. A specific harvest strategy framework that appropriate with the fishery characteristics has been developed. This paper describes the process of harvest strategy (HS) development for the tropical tuna in the Indonesia’s archipelagic waters (FMAs 713, 714 and 715). The HS is developed scientific works (including data collection, analysis/modelling and series technical and consultative stakeholder workshops as well as expert consultancies. Four technical workshops and seven stakeholder workshops have been done between 2015 and 2017. An interim HS (consisted of management objective, limit reference point, monitoring, analysis, harvest control rule and management measure) has been determined and agreed. Continues collaboration and commitment from related stakeholders including Government, fishers, fishing association, NGOs by adopting co-mangement and participatory approach in implementing the agreed harvest strategy, through data collection and sustain supports.The time series of catch and effort data, and size data could be used to monitor the fishery, stok status and its performance.In addition, involvement of relevant international tuna experts through expert consultancies are integrated process with the technical and stakeholder workshops. This HS development process is still on-going and can be refined, as HS development is a cycle process.